Rocks and trees : a photographic journey through the rich and varied geology, scenery and flora of the Sydney region - Martyn, John (Turramurra, NSW : STEP Inc, 2018)
A profusely illustrated descriptive book discribing the geological framework of the Sydney region and the vegetation communities supported by the different geological units.
Colour illustrations on endpapers.
Includes bibliographical references (pages 305-307) and index.
Keywords: Geology -- New South Wales -- Sydney Region -- Pictorial works; Natural history -- New South Wales -- Sydney Region -- Pictorial works; Landscape photography -- New South Wales -- Sydney Region -- Pictorial works; Earth Sciences, Geography, Environment, Planning; Nature & the natural world: general interest; Sydney Region (N.S.W.) -- Pictorial works; Sydney Region (N.S.W.) -- Environmental conditions -- Pictorial works; Australian